Constructing Donor–Acceptor-Linked COFs Electrolytes to Regulate Electron Density and Accelerate the Li+ Migration in Quasi-Solid-State Battery - Zhao, Genfu; Ma, Hang; Zhang, Conghui; Yang, Yongxin; Yu, Shuyuan; Zhu, Haiye; Sun, Yongjiang; Guo, Hong (Nano-Micro Letters, 2024)
Regulation the electronic density of solid-state electrolyte by donor–acceptor (D–A) system can achieve highly-selective Li+ transportation and conduction in solid-state Li metal batteries. This study reports a high-performance solid-state electrolyte thorough D–A-linked covalent organic frameworks (COFs) based on intramolecular charge transfer interactions. Unlike other reported COF-based solid-state electrolyte, the developed concept with D–A-linked COFs not only achieves electronic modulation to promote highly-selective Li+ migration and inhibit Li dendrite, but also offers a crucial opportunity to understand the role of electronic density in solid-state Li metal batteries. The introduced strong electronegativity F-based ligand in COF electrolyte results in highly-selective Li+ (transference number 0.83), high ionic conductivity (6.7 × 10–4 S cm−1), excellent cyclic ability (1000 h) in Li metal symmetric cell and high-capacity retention in Li/LiFePO4 cell (90.8% for 300 cycles at 5C) than substituted C- and N-based ligands. This is ascribed to outstanding D–A interaction between donor porphyrin and acceptor F atoms, which effectively expedites electron transferring from porphyrin to F-based ligand and enhances Li+ kinetics. Consequently, we anticipate that this work creates insight into the strategy for accelerating Li+ conduction in high-performance solid-state Li metal batteries through D–A system. Highlights: 1 Donor–acceptor-linked covalent organic framework (COF)-based electrolyte can not only fulfill highly-selective Li+ conduction, but also offer a crucial opportunity to understand the role of electronic density in quasi-solid-state Li metal batteries. 2 Donor–acceptor-linked COF electrolyte results in Li+ transference number 0.83, high ionic conductivity 6.7 × 10–4 S cm−1 and excellent cyclic ability in Li metal batteries. 3 In situ characterizations, density functional theory calculation and time-of-flight secondary ion mass spectrometry are adopted to expound the mechanism of the rapid migration of Li+ in the “donor–acceptor” electrolyte system.